Educação e Ascetismo Médico: as ofensivas a partir de Nietzsche. - Silva, Cleber Domingos Cunha da (2010)
The aim of this study is to demonstrate that as the doctor answers (responds) to the expectations of society in his task of promoting health, both he and those who are entrusted to him, develop a practice that I call medical asceticism. What the research tries to investigate is the pursuit of a healthy body as an ideal. The research was developed from the analysis of present speeches in platonic texts and its reflections in contemporary medical statements. The theoretical dialogue of the thesis emphasized the Nietzsche’s approach to the truth and moral. The arguments presented are divided in three books: 1- Medical Asceticism: a search of the truth as an ideal; 2- Medical scientific truth and moral and 3- Prognoses and prescriptions. Among the considerations pointed by the thesis, we checked the intersection between the practices of information and medical advisories and the search of a healthy life. The cult of the healthy life seems to be linked to the cult of the medical scientific truth and to the production of adjusted and submissive subjectivities. The medical ascetic ideal, observed in the production and consumption of truths appears like a demonstration of a game of forces, a will that Nietzsche called will to power.